RELIGIOUS CONFESSIONS IN THE INTERNET SPACE: RELIGIOUS ANALYSIS - N. L. Seitakhmetova,; Sh. M. Zhandossova,; T. T. Aimukhambetov,; Zh. Zh. Turganbayeva, (Scientific Journal of Pedagogy and Economics, 2019)
The relevance of the research topic is explained by the small number of articles and publications on this topic in the post-Soviet space. Attention is paid to the first studies of Western researchers. This article discusses Kazakhstan's Internet sources, as well as the very theme of religion in the Internet space. The modern world, which is characterized by diverse and large processes, is changing very quickly. The process of globalization is growing in the modern postmodern society, its structure is changing. The religious segment of the Internet has an increasing influence on the religious life of the society and gradually occupies an equal place in the religious media system, along with the press, radio and television. In the future, more detailed study of this subject is expected.